PERANCANGAN PERTANIAN VERTIKAL YANG TERINTEGRASI UNTUK MENGATASI MASALAH PANGAN MASA DEPAN - Caroline Natalie; Martin Halim (Jurusan Arsitektur dan Perencanaan, 2022)
Based on existing data, people in Indonesia will migrate to urban areas which will cause population problems. One of them is the food problem, coupled with the fast demand for fresh food in the capital, which lacks planting media and sunlight. Vertical agriculture is considered to be one solution to this problem. However, until now there has been no special building for vertical agriculture that stands in the capital. This is because to build a special building for vertical agriculture requires a large amount of cost and energy. The vertical design approach by rethinking the typology based on the analysis of existing studies produces a typology of open masses and blocks as edges, a typology of terracing and grid patterns, the placement of vertical farms in buildings using solar energy sources and technology (hybrids), and hydroponic, aquaponic, and hydroponic cultivation methods. and aeroponics with retail and office programs as supporting programs that are directly integrated with vertical farming as the main program. So that the